Critical Role of Etching Parameters in the Evolution of Nano Micro SLA Surface on the Ti6Al4V Alloy Dental Implants - Pankaj Chauhan (MDPI AG, 2021)
The surface of dental implants plays a vital role in early and more predictable osseointegration. SLA (sandblasted large grit and acid-etched) represents the most widely accepted, long-term clinically proven surface. Primarily, dental implants are manufactured by either commercially pure titanium (CP-Ti) or Ti6Al4V ELI alloy. The acid etch behavior of CP-Ti is well known and its effects on the surface microstructure and physicochemical properties have been studied by various researchers in the past. However, there is a lack of studies showing the effect of acid etching parameters on the Ti6Al4V alloy surface. The requirement of the narrow diameter implants necessitates implant manufacturing from alloys due to their high mechanical properties. Hence, it is necessary to have an insight on the behavior of acid etching of the alloy surface as it might be different due to changed compositions and microstructure, which can further influence the osseointegration process. The present research was carried out to study the effect of acid etching parameters on Ti6Al4V ELI alloy surface properties and the optimization of process parameters to produce micro- and nanotopography on the dental implant surface. This study shows that the Ti6Al4V ELI alloy depicts an entirely different surface topography compared to CP-Ti. Moreover, the surface topography of the Ti6Al4V ELI alloy was also different when etching was done at room temperature compared to high temperature, which in turn affected the behavior of the cell on these surfaces. Both microns and nano-level topography were achieved through the optimized parameters of acid etching on Ti6Al4V ELI alloy dental implant surface along with improved roughness, hydrophilicity, and enhanced cytocompatibility.